Understanding the Crisis in Somalia. Issue 1 (19th February 2014) - Zeid, Alaa Abou; Cochran, James J.
Abstract: The people of Somalia are suffering. The numbers are huge, but there is little real data. Even what little there is, painfully and dangerously gathered, points to where the most urgent needs may be. Alaa Abou Zeid and James J. Cochran look at the statistics of a disaster.